Clinical practice: Causation of term perinatal hypoxic-ischaemic basal ganglia and thalamus injury in the context of cerebral palsy litigation: Position statement - Bhorat, I; Buchmann, E; Frank, K; Soma-Pillay, P; Nicolaou, E; Pistorius, L; Smuts, I (South African Medical Journal, 2023)
Basal ganglia and thalamus (BGT) hypoxic-ischaemic brain injury is currently the most contentious issue in cerebral palsy (CP) litigation in South Africa (SA), and merits a consensus response based on the current available international literature. BGT pattern injury is strongly associated with a preceding perinatal sentinel event (PSE), which has a sudden onset and is typically unforeseen and unpreventable. Antepartum pathologies may result in fetal priming, leading to vulnerability to BGT injury by relatively mild hypoxic insults. BGT injury may uncommonly follow a gradual-onset fetal heart rate deterioration pattern, of duration ≥1 hour. To prevent BGT injury in a clinical setting, the interval from onset of PSE to delivery must be short, as little as 10 - 20 minutes. This is difficult to achieve in any circumstances in SA. Each case needs holistic, multidisciplinary, unbiased review of all available antepartum, intrapartum and postpartum and childhood information, aiming at fair resolution without waste of time and resources.